2015
DOI: 10.14200/jrm.2015.4.0105
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Rosmarinic Acid on Immunological and Neurological Systems: A Basic Science and Clinical Review

Abstract: Rosmarinic acid (RosA) is an ester of caffeic acid and 3,4-dihydroxyphenylactic acid. RosA has a number of beneficial biological activities, including antiviral, antibacterial, anti-inflammatory, and antioxidant properties. Oxidative stress is recognized as a common factor in many neurodegenerative diseases and is a proposed mechanism for age-related degenerative processes as a whole. RosA has shown antioxidative action, acting as a scavenger of free radicals. RosA protects neurons from oxidative stress, signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 34 publications
0
17
0
1
Order By: Relevance
“…The main constituent of Rosemary (Rosemarinus officinalis L.) leaves, Rosmarinic acid, has solubility, which can dissolve in ethanol solvents but is not soluble in n-hexane and is slightly soluble in ethyl acetate. [6,8] The n-Hexan solvent aims to attract all nonpolar compounds contained in Rosmary leaves while ethyl acetate functions to attract other nonpolar and semipolar compounds. While ethanol serves to attract polar compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The main constituent of Rosemary (Rosemarinus officinalis L.) leaves, Rosmarinic acid, has solubility, which can dissolve in ethanol solvents but is not soluble in n-hexane and is slightly soluble in ethyl acetate. [6,8] The n-Hexan solvent aims to attract all nonpolar compounds contained in Rosmary leaves while ethyl acetate functions to attract other nonpolar and semipolar compounds. While ethanol serves to attract polar compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitory effects of rosemary ( R. officinalis ) ethanolic extract on Propionibacterium acnes -induced inflammation has been documented in vitro , and attributed to suppression of pro-inflammatory cytokines (interleukin [IL]-8, IL-1β and tumor necrosis factor [TNF]-α) in the monocytic THP-1 cell line, along with in vivo attenuation of the P. acnes- induced ear swelling and granulomatous inflammation in an intradermally injected mouse model, via suppression of nuclear factor kappa-B (NF-κB) and Toll-like receptor -2 (TLR-2) mediated signaling pathways (Tsai et al , 2013). In the same context, Friedman (2015) pointed out that the concentrations of TNF-α, interferon-γ, IL-6 and IL-12 were decreased in infected animals treated with RA when compared with infected animals without RA. Neuropathic pain due to chronic constriction injury of sciatic nerves in rats was tested with RA, and it was found that there was pain relief due to the anti-inflammatory effect of RA (Ghasemzadeh Rahbardar et al , 2017).…”
Section: Analgesic and Anti-inflammatory Effectsmentioning
confidence: 98%
“…Beneficial polyphenols such as RA, carnosic acid and carnosol present in the rosemary herb also have immunomodulatory effects (Chun et al , 2014; Rocío-Teruel et al , 2015). The immunomodulatory impacts of RA may also make it a novel agent for the treatment of autoimmune disorders (Friedman, 2015). The use of RA at a concentration of 100 or 200 mg oil kg −1 of broiler chicken diet, increased immunologic indices like phagocytic activity and phagocytic index along with the concentrations of some biochemical blood parameters like triglycerides, total cholesterol, low density lipoprotein and high-density lipoprotein.…”
Section: Immunomodulatory Effectsmentioning
confidence: 99%
“…However, comparable levels were reported from other species [ 37 , 38 ]. Rosmarinic acid exerts a variety of well-documented pharmacological properties, such as antioxidant, anti-inflammatory, antibacterial, anti-angiogenic, anti-mutagenic, antidepressant, and neuroprotective, as well as antiallergenic [ 39 , 40 , 41 , 42 , 43 ]. Due to a high content of rosmarinic acid, such properties can also be attributed to whole extracts or tinctures of lungwort.…”
Section: Resultsmentioning
confidence: 99%